Peningkatan Pengetahuan Gizi dan Kesehatan Melalui Pengenalan Ubi Ungu sebagai Pangan Fungsional di Lingkungan Sekolah - Siahaan, Reny Yuliana; Siahaan, May Frinsiska; Tambunan, Herlina Yolanda (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service activity aims to enhance the knowledge and skills of the local community, particularly elementary school students and teachers, in recognizing and processing purple sweet potatoes as a nutritious and economically valuable local food ingredient. Purple sweet potatoes were introduced as a superfood due to their rich nutritional content, including anthocyanins, vitamin C, and dietary fiber, which offer various health benefits. Through a series of educational sessions and hands-on demonstrations on how to make purple sweet potato pudding, participants were provided with knowledge about its nutritional benefits, food processing techniques, and basic marketing strategies. The results of the program showed an increase in participant enthusiasm and understanding regarding the diversification of local food products. In addition to producing a healthy and appealing pudding product, the activity also encouraged the use of local food resources as a potential home-based business. It is expected that this initiative will inspire continuous development of food innovation based on local ingredients and contribute to improving the community's economic well-being in a sustainable manner.